Teleworkability and the COVID-19 crisis: a new digital divide? - Matteo Sostero; Santo Milasi; John Hurley; Enrique Fernández-Macías; Martina Bisello (European Commission, Joint Research Centre (JRC), 2020)
The paper discusses the extent of teleworking in the EU before and during the COVID-19 outbreak, develops a conceptual analysis to identify the jobs that can be done from home and those that cannot, and on this basis quantifies the fraction of employees that are in teleworkable occupations across EU countries, sectors and socio-economic profiles. Using the occupational task descriptions provided in the Italian Indagine Campionaria delle Professioni, with additional indicators from the European Working Conditions survey, we estimate that 37% of dependent employment in the EU is currently teleworkable - very close to the estimates of teleworking indicated in real-time surveys during the COVID-19 crisis. Because of differences in the employment structure, the fraction of telewokable employment ranges between 33-44% in all but five EU member states. Even starker differences in teleworkability emerge between high- and low-paid workers, between white- and blue-collar workers, as well as by gender. Results suggests that that the large expansion of telework since the COVID-19 outbreak has been strongly skewed towards high-paid white-collar employment. Yet, enforced closures have likely resulted in many new teleworkers amongst low and mid-level clerical and administrative workers who previously had limited access to this working arrangement. This is consistent with the evidence showing that, beyond differences in the industrial and occupational structures, the pre-outbreak large differences in telework prevalence across EU countries were largely driven by other factors, notably the organisation of work, regulation, and management culture. This paper also discusses some policy implications that the current experience of telework may have for the future of work.
Keywords: 330; Teleworking; remote work; work from home; tasks; COVID-19